2024
DOI: 10.1039/d3ta06708d
|View full text |Cite
|
Sign up to set email alerts
|

Segregation and interdiffusion processes in perovskites: a review of recent advances

Natalia Porotnikova,
Denis Osinkin

Abstract: This review focuses on recent advances in the study of segregation processes, namely modeling, segregation on single and polycrystalline samples, effects of polarization, interdiffusion, different atmospheres and exsolution of nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 274 publications
0
3
0
Order By: Relevance
“…The degradation of the single cell is due most likely to the coarsening of the impregnated LSCF nanoparticles, which is possibly due to the lack of strong interaction between the nanoparticles and scaffolds [50,51]. In addition, the high tendency for Sr surface segregation and its migration and interaction with 8YSZ under cathodic polarization could be another reason for the degradation of the cathode [52,53]. On the other hand, Ni coarsening has been considered as the most detrimental degradation mechanism in SOFC anode electrodes, which may also lead to worse stability with both reduced TBP sites and electrical conductivity [54].…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…The degradation of the single cell is due most likely to the coarsening of the impregnated LSCF nanoparticles, which is possibly due to the lack of strong interaction between the nanoparticles and scaffolds [50,51]. In addition, the high tendency for Sr surface segregation and its migration and interaction with 8YSZ under cathodic polarization could be another reason for the degradation of the cathode [52,53]. On the other hand, Ni coarsening has been considered as the most detrimental degradation mechanism in SOFC anode electrodes, which may also lead to worse stability with both reduced TBP sites and electrical conductivity [54].…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…SrFeO 3−δ -based materials are the most widely studied for cathodes in iron-based systems. Other researchers have shown that the structure of SrFeO 3−δ varies significantly with the temperature and oxygen partial pressure [24][25][26][27][28][29][30][31][32][33][34][35][36]. Jiang et al introduced high-valence Nb into Fe and found that the modification of Nb enhanced the stability of the crystal and effectively avoided the phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…The cobaltites that usually contain alkaline earth metal oxides are plagued by cation surface segregation, leading to a reduction in active surface and degradation in stability over time. The surface segregated alkaline oxides such as SrO and BaO possess a Smith acidity scale of −9.4 and −10.8, and the removal of these species based on acid–base reaction principle has been identified as an effective strategy to address this issue. Zhuang et al used the acidic oxide Mn 2 O 3 to capture the segregated SrO on the LSCF surface, creating Sr defects and additional oxygen vacancies on the surface and thereby enhancing the electrochemical performance and stability of LSCF .…”
Section: Introductionmentioning
confidence: 99%